Integration of AI and OR techniques in constraint programming : 13th International Conference, CPAIOR 2016, Banff, AB, Canada, May 29-June 1, 2016, Proceedings /: 13th International Conference, CPAIOR 2016, Banff, AB, Canada, May 29-June 1, 2016, Proceedings. (2016) - Unknown
No abstract available